Enterprise Architecture for Integration of Demand-Responsive Services in Public Transport - Mark-Oliver Würtz; Kurt Sandkuhl (Complex Systems Informatics and Modeling Quarterly)
The popularity of new mobility services (NMS), like car sharing, urban bikes or e-scooters, is increasing in many urban areas. In comparison to traditional supply-oriented public transport with defined timetables and transportation routes, NMS are demand-responsive services aiming to meet the ad-hoc needs of users. NMS have started to influence the way people move in urban areas, and they also have an impact on public transport operators which begin to offer their own NMS or integrate the services of established NMS operators. This article investigates the changes implied by NMS for the enterprise architecture (EA) of public transport operators. The paper presents and evaluates an EA approach for integrating demand-responsive services into traditional supply-oriented public transport. We propose a partial enterprise architecture as an extension of the established ITVU core model, which is an established reference model in the public transportation domain. Although EA management is recognised as relevant for public transport companies, there is a lack of such an extension addressing NMS integration. The contribution of this article are to (1) offer an overview of the state of research in enterprise architectures for public transport, (2) make a case study for illustrating the challenges and requirements of NMS integration, (3) provide a first version of the partial (core) reference EA for integration of NMS including an initial evaluation.